SISTEM PEMERINTAHAN INDONESIA : FUNGSI DAN KEWENANGAN LEMBAGA NEGARA SERTA OTONOMI DAERAH - Krisanta Lusia Iju; Amanda M.J. Laning; Kevy Listiana Fransisca Taneo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesia's governance system still shows a significant gap between the ideal presidential concept, based on Pancasila, and the reality on the ground where the executive branch dominates everything. Institutions like the Regional Representatives Council (DPD) prove to be weak in controlling regional affairs, while regional autonomy is often hindered by massive cancellations of local regulations and financial imbalances between provinces. This research uses a mixed explanatory sequential approach in 10 selected provinces (period 2018-2024), with primary data from 30 interviews and direct observations combined with additional data from the Central Statistics Agency and the Ministry of Finance. Through panel regression analysis and content analysis, this study reveals crucial facts: the DPD essentially functions only as a rubber stamp for the executive, fund transfers from the center create a financial illusion, and regional autonomy remains merely formal without real substance. From these findings, an asymmetric autonomy model emerges with three core pillars: digital DPD, tiered regional authority hierarchy, and a Pancasila verification mechanism by the Constitutional Court. The proposed recommendations include revising Article 22D of the 1945 Constitution, laws on asymmetric autonomy, and a pilot project in Papua in 2027 to realize more equitable and prosperous democratic governance.